Nonlinear parameter identification of timber-concrete composite beams using long-gauge fiber optic sensors - Hong, Wan (2020)
A novel method for nonlinear parameter identification of partially composite beams using long-gauge strain responses is proposed in this paper. Firstly, theoretical analysis shows that neutral axis position of timber beam and concrete slab can be estimated by measured long-gauge strain and material properties. Then, distribution of curvature, bending stiffness, deflection and interface slip can be determined by identified neutral axis position. Secondly, timber-concrete composite beams connected by ductile connectors with different degree of composite action are designed to verify the presented method. Experimental results show that the estimated parameters (neutral axis position, bending stiffness and interface slip) can clearly reflect and quantify the deterioration process of partially composite beams. Meanwhile, both global and local responses can be predicted by long-gauge strain sensors. The predicted responses (deflection at mid-span and strain along the beam height) agree well with the test results when partially composite action is considered, the errors will be unacceptable without considering partially composite action. Hence, the presented method can be utilized for better understanding of mechanical properties of partially composite beams and performance assessment of existing composite structures.